Evaluation of anti-osteoarthritic activity of hydroalcoholic extract of Moringa oleifera by using papain-inducing model in experimental animals - Vaibhav Sangameshwar Gavane; Snehal Ambadas Gojare; Deepti Dinesh Bandawane (Journal of Complementary and Integrative Medicine, 2026)
Abstract Background The anti-inflammatory, anti-arthritic, and antioxidant qualities of Moringa oleifera have long been used to treat inflammation and various types of arthritis. Objectives To evaluate the hydroalcoholic extract of Moringa oleifera pods in a papain-induced animal model. Materials and methods Hydroalcoholic extraction was used to obtain the hydroalcoholic extract of Moringa oleifera (HEMO), and its phytochemical constituents were examined. In Wistar rats, osteoarthritis was induced by intra-articular injection using a Papain-induced model, and Glucosamine sulfate was used as a conventional standard treatment. Experimental animals were given HEMO pods at 100 mg/kg and 200 mg/kg orally. Knee joint diameter, joint stiffness score, locomotor activity, body weight, and post-sacrifice Biochemicals like Matrix Metalloproteins-13, C-Reactive Proteins, Alkaline Phosphatase, Sodium Dismutase, Catalase (MMP-13, CRP, ALP, SOD, CAT), Haematological – Erythrocyte Sedimentation Rate (ESR), Cytokines like Interleukin-1β and Tumour Necrosis Factor-α (IL-1β, TNF-α), radiological, and histopathological markers were done to assess anti-osteoarthritic activity of extract. Results Hydroalcoholic extract of Moringa oleifera (HEMO) at 200 mg/kg significantly reduced knee diameter and joint stiffness in papain-induced arthritic rats by upregulating antioxidant agents and downregulating inflammatory mediators. In addition, the chondroprotective activity of the HEMO 200 mg/kg extract against OA was validated by histological and radiographic (X-ray) assessments, thereby scientifically confirming the traditional use of HEMO in the management of inflammation and osteoarthritis. The hypothesis that HEMO can be used to treat arthritis is adequately supported based on these standards of evidence. Conclusions In the research, HEMO at a dosage of 200 mg/kg revealed a significant anti-arthritic effect, confirming its conventional usage. The results offer sufficient preclinical validation for potential therapeutic use. These results indicate that HEMO may potentially be used as a natural treatment for managing inflammation and arthritis.